Cognitive deficits persisting in patients with alcohol dependence syndrome after detoxification - Ankur Sachdeva; Mina Chandra; Shilpa Khullar; Syed Zafar Abbas (Industrial Psychiatry Journal)
Background: Alcohol-related cognitive deficits (ARCDs) have received little clinical recognition due to doubts regarding the etiopathogenesis and lack of consensus in the diagnostic guidelines. Aim: The present study aimed at evaluating the pattern of cognitive deficits in patients of alcohol dependence without dementia, and assessing the relationship between these subtle cognitive deficits and alcohol use parameters. Materials and Methods: The study included randomly selected, consenting, non-delirious patients of alcohol dependence syndrome (ADS) without dementia, admitted in the de-addiction ward. Cognition was assessed by Mini Mental State Examination (MMSE) of the Diagnostic Interview for Genetic Studies at admission and after 7 days of detoxification. “T-test” was used to assess cognitive improvement and residual deficits, while correlation analysis was used to compare the relationship between alcohol use parameters and MMSE scores. Results: We recruited 63 male patients with mean age of 38.62 (±9.61) years. Significant improvement was noted in cognition post-detoxification. However, most of the subjects had subtle cognitive deficits which may fall within the realm of ARCD, mainly in domains of attention/concentration, recall, language, and visuo-constructional skills (P < 0.05). The cognitive deficits correlated with duration and severity of alcohol dependence (P < 0.05), however, were independent of daily alcohol quantity. Conclusion: Subtle cognitive deficits may persist in patients of ADS without dementia, even after successful detoxification. They may be easily missed despite contact with mental health professionals, as these deficits may only be evident on neuro-psychological testing.